Prove that (tan⁑ A  + sin ⁑A)/(tan⁑ A - sin ⁑A ) = (sec A + 1)/(sec A - 1)

Question 30 (OR 2nd question).jpg

Question 30 (OR 2nd question) slide 2.jpg

  1. Class 10
  2. Solutions of Sample Papers for Class 10 Boards

Transcript

Question 30 (OR 2nd question) Prove that (tan⁑〖𝐴 γ€—+γ€– sin〗⁑𝐴)/(tan⁑〖𝐴 γ€—βˆ’γ€– 𝑠𝑖𝑛〗⁑𝐴 ) = (𝑠𝑒𝑐 𝐴 + 1)/(𝑠𝑒𝑐 𝐴 βˆ’ 1) Solving LHS (tan⁑〖𝐴 γ€—+γ€– sin〗⁑𝐴)/(tan⁑〖𝐴 γ€—βˆ’γ€– 𝑠𝑖𝑛〗⁑𝐴 ) Writing everything in terms of sin A and cos A = (sin⁑〖 𝐴〗/cos⁑〖 𝐴〗 + sin⁑〖 𝐴〗)/(sin⁑〖 𝐴〗/cos⁑〖 𝐴〗 βˆ’γ€– sin〗⁑〖 𝐴〗 ) = ((sin⁑〖 𝐴〗 + sin⁑𝐴 cos⁑𝐴)/cos⁑〖 𝐴〗 )/((sin⁑〖 𝐴〗 βˆ’ sin⁑𝐴 cos⁑𝐴)/cos⁑〖 𝐴〗 ) = (sin⁑〖 𝐴〗 + sin⁑𝐴 cos⁑𝐴)/(sin⁑〖 𝐴〗 βˆ’ sin⁑𝐴 cos⁑𝐴 ) Taking sin A common = (sin⁑𝐴 (1 + cos⁑𝐴 ))/(sin⁑𝐴 (1 βˆ’ cos⁑𝐴 ) ) = ((1 + cos⁑𝐴 ))/( (1 βˆ’ cos⁑𝐴 ) ) Taking cos A common = (cos⁑〖 𝐴〗 (1/cos⁑𝐴 + 1))/(cos⁑〖 𝐴〗 (1/cos⁑𝐴 βˆ’ 1) ) = ( (1/cos⁑𝐴 + 1))/( (1/cos⁑𝐴 βˆ’ 1) ) = (𝑠𝑒𝑐 𝐴 + 1)/(𝑠𝑒𝑐 𝐴 βˆ’ 1) = RHS Hence proved

About the Author

Davneet Singh's photo - Teacher, Computer Engineer, Marketer
Davneet Singh
Davneet Singh is a graduate from Indian Institute of Technology, Kanpur. He has been teaching from the past 9 years. He provides courses for Maths and Science at Teachoo.